A proteção das nascentes em áreas urbanas consolidadas: dispensável ou necessária missão? - Souza, Samara Rached (Universidade Federal de São Carlos, 2018)
The territory of the city of Sorocaba/SP is marked by a dense water mesh, and one of the sub-basins that make up the main water courses is Ribeirão do Lajeado, also known as Água Vermelha, affluent from the left bank of the river Sorocaba placed in a consolidated urban area. The present paper has generated an Environmental Impact Index in Ribeirão do Lajeado’s Water Springs. For this purpose, it has been performed on the field a macroscope diagnosis of the water springs, being that every evaluated parameter received a grade (from 1 to 3) for its later classification. On this evaluation, the following parameters have been verified: color, odor, existence of garbage on the banks, existence of floating materials, foam, oil, sanitary sewer, state of vegetation, human presence and animal presence in the Permanent Preservation Area, protection of the area and proximity to residence or establishments. The results showed that all the visited places are impacted by the urbanization, being the strongest indicative for that, the amount of garbage found on those places. Color, odor, foam, floating materials and oil, in general, were positively highlighted, but sewer and human presence had recurrent negative results. The most alarming verified parameters are related to the water springs proximity to establishments, nonexistent protection of the area, the Permanent Preservation Area that does not meet the 50 meters laid out in law nº 12.651/12 of the Forestry Code. The generated Environmental Impact index has classified the water springs as “reasonable”. “bad” or “terrible”, without getting any classification “great” or “good” propitiating a debate around the water resources conservation subject and if they are important in the context of urban basins, besides instigating deeper researches in the Ribeirão do Lajeado sub-basin to indicate its integrity and promote conservation actions of the springs.
The protection of spring waters in consolidated urban areas: dispensable or necessary mission?
Keywords: Hidrologia urbana; Diagnóstico macroscópico; Conservação; Recursos hídricos; Urban hidrology; Macroscope diagnosis; Water resources; Conservation; CIENCIAS BIOLOGICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS